Latent HIV dynamics and implications for sustained viral suppression in the absence of antiretroviral therapy - John M. Murray (Elsevier, 2018)
Objectives: The interaction between HIV and the immune system gives rise to a complex dynamical system. We therefore investigate whether delayed viral rebound after antiretroviral therapy (ART) interruption (ATI) may be due to an individual's viral-immune state being in a region of relative stability, and if so, how this can be extended. Methods: Using a mathematical model duplicating plasma viral levels, HIV DNA and immune homeostatic dynamics for individuals on ART commenced at either primary (PHI) or chronic (CHI) HIV infection, we investigate whether latent reservoir reductions and perturbations in other infected and uninfected memory CD4+ T cell subsets can delay viral rebound. Results: Solely decreasing the latent reservoir did not delay rebound unless ART was commenced at PHI. If ART was commenced at CHI, latent reservoir reductions paired with depletions of each of uninfected resting and activated cells could delay rebound indefinitely. Starting ART at PHI resulted in easier suppression if the reservoir was reduced in combination with each of six infected and uninfected subsets. Although these paired reductions maintained viral suppression, an opportunistic infection that increased activation to suitably high levels can lead to viral rebound. Conclusions: If viral rebound is purely a stochastic process, suppression after an ATI requires reduction of the latent reservoir to extremely low levels. On the other hand, if suppression of the viral-immune system is due to stability properties of this complex system, then achievable latent reservoir reductions can lead to long-term suppression if combined with other cell subset modifications.